Improved maternal–fetal outcomes among emergency obstetric referrals following phone call communication at a teaching hospital in south western Uganda: a quasi-experimental study - Kanyesigye, Hamson; Kabakyenga, Jerome; Mulogo, Edgar; Fajardo, Yarine; Atwine, Daniel; MacDonald, Noni E.; Bortoluss, Robert; Migisha, Richard; Ngonzi, Joseph (BMC Pregnancy and Childbirth, 2022)
Background: Emergency obstetric referrals develop adverse maternal–fetal outcomes partly due to delays in offering appropriate care at referral hospitals especially in resource limited settings. Referral hospitals do not get prior communication of incoming referrals leading to inadequate preparedness and delays of care. Phone based innovations may bridge such communication challenges. We investigated effect of a phone call communication prior to referral of mothers in labour as intervention to reduce preparation delays and improve maternal–fetal outcome at a referral hospital in a resource limited setting. Methods: This was a quasi-experimental study with non-equivalent control group conducted at Mbarara Regional Referral Hospital (MRRH) in South Western Uganda from September 2020 to March 2021. Adverse maternal–fetal outcomes included: early neonatal death, fresh still birth, obstructed labour, ruptured uterus, maternal sepsis, low Apgar score, admission to neonatal ICU and hysterectomy. Exposure variable for intervention group was a phone call prior maternal referral from a lower health facility. We compared distribution of clinical characteristics and adverse maternal–fetal outcomes between intervention and control groups using Chi square or Fisher’s exact test. We performed logistic regression to assess association between independent variables and adverse maternal–fetal outcomes. Results: We enrolled 177 participants: 75 in intervention group and 102 in control group. Participants had similar demographic characteristics. Three quarters (75.0%) of participants in control group delayed on admission waiting bench of MRRH compared to (40.0%) in intervention group [p= Conclusion: The phone call intervention resulted in reduced delay to patient admission at a tertiary referral hospital in a resource limited setting, and is protective against adverse maternal–fetal outcomes. Incorporating the phone call communication intervention in the routine practice of emergency obstetric referrals from lower health facilities to regional referral hospitals may reduce both maternal and fetal morbidities
Keywords: Phone call; Communication; Intervention; Emergency; Obstetric referral; Quasi-experimental; Maternal– fetal outcomes